Life Phases of Canon – Exemplified by Socialist Realism - Hans Günther (Slovenska Literatura, 2013)
The presented article enters into the professional discussion with several goals. On the one hand, it has the ambition to introduce Socialist Realism in the context of German literary-historical reflection and, on the other hand, the article offers new stimuli useful in thinking about the history of Slovak literature in the 20th century. The study draws attention to the phases of life or existence of the canon, especially in relation to Socialist Realism. The author contemplates about five stages of its fulfilment in the context of Soviet literature. Against a background of social-political changes he questions the (non)autonomous literary life and outlines the struggle of literature for emancipation from the prescribed canonical doctrine. The study interlinks partial knowledge of the canon and its positions in forming human culture and, of Socialist Realism, which gained the status of the official doctrine in Slovak literature, too. The article makes space for confrontation between the subject in question and the domestic literary-historical reflection.